2009
DOI: 10.1016/j.neuron.2009.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Neurons that Fire Together Also Conspire Together: Is Normal Sleep Circuitry Hijacked to Generate Epilepsy?

Abstract: Summary Brain circuits oscillate during sleep. The same circuits appear to generate pathological oscillations. In this review we discuss recent advances in our understanding of how epilepsy co-opts normal, sleep-related circuits to generate seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
379
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(390 citation statements)
references
References 199 publications
(276 reference statements)
10
379
0
1
Order By: Relevance
“…This configuration is different from the Pyramidal cell Inhibitory Network Gamma (PING) mechanism, where a reciprocal interaction between the two cell types generates gamma oscillations [63] at a lower frequency, and also for the thalamic generation of spindles [4], where similar excitatoryinhibitory out of phase firing generates the oscillation. The synchronized GABAA receptor-mediated currents from the PVBCs give rise to a major component of the ripple-frequency oscillation in the local field potential, and phase-modulate the rather sparse tonic spiking of pyramidal cells, which also contribute somewhat to the ripple local field potential.…”
Section: Epileptic Activity and Pathological Fast Ripplesmentioning
confidence: 84%
See 1 more Smart Citation
“…This configuration is different from the Pyramidal cell Inhibitory Network Gamma (PING) mechanism, where a reciprocal interaction between the two cell types generates gamma oscillations [63] at a lower frequency, and also for the thalamic generation of spindles [4], where similar excitatoryinhibitory out of phase firing generates the oscillation. The synchronized GABAA receptor-mediated currents from the PVBCs give rise to a major component of the ripple-frequency oscillation in the local field potential, and phase-modulate the rather sparse tonic spiking of pyramidal cells, which also contribute somewhat to the ripple local field potential.…”
Section: Epileptic Activity and Pathological Fast Ripplesmentioning
confidence: 84%
“…Therefore, PVBCs will receive excitation that drives them into depolarization block (and their already weakened transmission breaks down due to strong short-term depression), resulting in an uncontrolled burst firing in all PCs [22,70]. The similarities between these phenomena suggests that IIS are degenerate forms of SWR and, as concluded previously [4], "epileptic events hijack normal circuitry".…”
Section: Generation Of Interictal Spikes: Changes In Cellular and Netmentioning
confidence: 98%
“…Aroused brain states are indeed associated with significantly increased seizure resistance (Kotagal and Yardi, 2008;Beenhakker and Huguenard, 2009) and there is a well-established relationship between arousal, cortical activation, and the cholinergic system. For example topically applied scopolamine to exposed feline cortex lead to the development of seizures but was prevented by application of the acetylcholinesterase inhibitor physostigmine (Tan et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Thalamocortical network oscillations are often observed to be accompanied by a shift in the firing pattern of thalamocortical (TC) neurons from tonic to burst firing (16). Low-threshold burst firing driven by T-type Ca 2ϩ currents in TC neurons has long been proposed to be a critical component in sustaining the oscillations during the SWDs (3,8,17), although a controversy still remains (4, 18).Many studies have described spontaneous appearance of SWDs in the cortical EEG from rodent models for absence epilepsy (19)(20)(21)(22)(23)(24). Some showed that T-type Ca 2ϩ currents were increased in the TC neurons of mutant mice with spontaneous absence epilepsy (25-27).…”
mentioning
confidence: 99%
“…Thalamocortical network oscillations are often observed to be accompanied by a shift in the firing pattern of thalamocortical (TC) neurons from tonic to burst firing (16). Low-threshold burst firing driven by T-type Ca 2ϩ currents in TC neurons has long been proposed to be a critical component in sustaining the oscillations during the SWDs (3,8,17), although a controversy still remains (4, 18).…”
mentioning
confidence: 99%